Cathy Ames as a Femme Fatale in East of Eden: Steinbeck and Kazan - Tomasz Śledź (Polish Journal of English Studies)
Through the lens of the femme fatale trope, this article compares the portrayal of Cathy Ames from John Steinbeck’s East of Eden in the novel and the 1955 film adaptation directed by Elia Kazan. The text explores the perception of the femme fatale framework through the history of literary criticism and showcases how frequently it can be observed in a variety of texts. The character of Cathy Ames displays many characteristics typical for the framework, such as the fluidity of identity and class. She is an established villain of the book’s story, and her actions greatly influence the narrative. The validity of her character and her purpose in the book have been greatly debated by literary critics. Elia Kazan’s 1955 film adaptation changes her portrayal substantially; she is no longer a straightforward antagonist. The film problematizes her role and challenges the classic understanding of the femme fatale trope. This article exemplifies the changes made to her character through the analysis of specific scenes in relation to cinematography, acting, and alterations in the plot. It also analyzes how the medium of film influences characterization and transposition of information. The aim of the article is to explore the attributes of the femme fatale trope, as it is a term used frequently in relation to cultural texts, yet elusive in definition. The nature of film adaptations is also considered in the article, as it might help understand why filmmakers frequently make changes to the source material, which consequently result in works vastly different from the adapted material.